2023
DOI: 10.7324/jabb.2023.70862
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable biodegradation of textile dye reactive blue 222 by the novel strain Enterobacter CU2004, isolated from the industrial waste: A design of experiment based optimization study and characterisation of metabolites

Vasantha Veerappa Lakshmaiah,
Anish Nag,
Suresh Gotekar
et al.

Abstract: Reactive Blue 222 (RB222) is widely used in textile industries and hence a common recalcitrant pollutant in the industrial effluent. Bioremediation of this dye is of significance as its one of the complex dyes with high molecular weight. In the present study, we isolated a novel bacterial strain Enterobacter CU2004 from the industrial waste and characterize using16S rRNA gene sequencing. Its potential to dye degradation was evaluated in a simple minimal salt media with the parameters namely dye concentration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Previous studies highlighted the effect of temperature on decolorization rate and how temperature can affect the microbe’s physiology [ 85 , 87 – 90 ]. Our results are in harmony with those of Khan and Malik, who also observed an increased bio-decolorization rate of RB5 dye in the mesophilic temperature range [ 91 , 92 ]. Endo (2003) reported that at 40 °C, Streptomyces sp.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies highlighted the effect of temperature on decolorization rate and how temperature can affect the microbe’s physiology [ 85 , 87 – 90 ]. Our results are in harmony with those of Khan and Malik, who also observed an increased bio-decolorization rate of RB5 dye in the mesophilic temperature range [ 91 , 92 ]. Endo (2003) reported that at 40 °C, Streptomyces sp.…”
Section: Discussionsupporting
confidence: 92%
“…While, Vinayak and Singh [ 39 ] showed that the best carbon source was glucose, followed by sucrose and fructose, in the bio-decolorization of Evans blue azo dye using four different Streptomyces spp. In contrast, Lakshmaiah et al [ 92 ] reported lactose to be the best carbon source and yeast extract to be the best nitrogen source for the bio-decolorization of reactive blue 222 azo dye by Kucoria marina CU2005.…”
Section: Discussionmentioning
confidence: 97%
“…This isolate is a viable candidate for bioremediation because of its expansive potential in building a cost-effective, efficient, and scalable microbial dye-degrading process. 40 Over the past few decades, the use of microorganisms for bioremediation has gained increasing attention. Multiple microorganisms, including bacteria and fungi, exhibit a promising ability to decolorize melanoidincontaining wastewater from the distillation industry.…”
Section: Effect Of Peptone Concentration On Melanoidin Decolorizationmentioning
confidence: 99%